Evaluation of Genotoxic effects of Chromium on tannery workers by various Cytogenetic assays - Rahman, Mohammad Habibur (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2009